Metaheuristics for maritime operations - Homayouni, S. Mahdi; Fontes, Dalila B. M. M. (Computer engineering series (London, England) Optimization heuristics set, 2018)
Metaheuristic Algorithms in Maritime Operations Optimization focuses on the seaside and port side problems regarding the maritime transportation. The book reviews and introduces the most important problems regarding the shipping network design, long-term and short-term scheduling and planning problems in both bulk and container shipping as well as liquid maritime transportation. Application of meta heuristic algorithm is important for these problems, as most of them are hard and time-consuming to be solved optimally.'